Formation of Wrinkled Nanostructures via Surface–Bulk Curing Disparity in Ethyl Cyanoacrylate: Toward Superhydrophobic Surface Applications - Changwoo Lee; Heon-Ju Choi; Kyungeun Jeong; Kyungjun Lee; Handong Cho (Nanomaterials)
Superhydrophobic surfaces, known for their exceptional water-repellent properties with contact angles exceeding 150°, are highly regarded for their effectiveness in applications including self-cleaning, antifouling, and ice prevention. However, the structural fragility and weak durability of conventional coating limit their long-term use. In this research, a new approach is proposed for the fabrication of long-lasting superhydrophobic surfaces using ethyl cyanoacrylate (ECA) and a primer. The application of the primer creates a curing rate disparity between the surface and bulk of the ECA layer, resulting in the formation of wrinkled microstructures essential for achieving superhydrophobicity. The fabricated surfaces were further functionalized through plasma treatment and hydrophobic silane (OTS) coating, enhancing their water-repellent properties. This straightforward and scalable method produced surfaces with excellent superhydrophobicity and robust adhesion to substrates. Durability tests, including roller abrasion and microscratch evaluations, indicated that the wrinkled structure and strong substrate adhesion contributed to sustained performance even under mechanical stress. Additionally, mechanical properties were assessed through nanoindentation, demonstrating enhanced resistance to physical damage compared to conventional superhydrophobic coatings. This study highlights the potential of ECA-based superhydrophobic surfaces for applications requiring durability and mechanical stability, such as architectural coatings, automotive exteriors, and medical devices. The approach offers a promising solution to the limitations of existing superhydrophobic technologies and opens new avenues for further research into wear-resistant and environmentally resilient coatings.